2014
DOI: 10.1039/c4fo00181h
|View full text |Cite
|
Sign up to set email alerts
|

Sensory attributes of soft drinks and their influence on consumers' preferences

Abstract: Soft drinks are beverages composed of water and other ingredients that provide specific sensorial attributes. Soft drink consumption patterns have recently been changed partially influenced by an increased availability of different types of beverages during the last few years. Consumers' preferences to choose one drink over another are influenced, not only by genetic, psychological and environmental factors, but also by the beverage's specific attributes. In fact, beverage consumption is driven by the sensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…The assessors observed that the carbonation of these beverages positively improved the taste and flavour of the beverages by imparting the fizzy taste on them. Similar results were obtained by Redondo et al [20], who pointed out that carbonated carrot juice maintained a better taste by the impartation of a 'fizzy' taste to the juice. Redondo et al [20] also pointed out that one of the sensory attributes of soft drinks is the impartation of a fizzy taste sensation when these beverages are consumed.…”
Section: Sensory Evaluationsupporting
confidence: 88%
See 1 more Smart Citation
“…The assessors observed that the carbonation of these beverages positively improved the taste and flavour of the beverages by imparting the fizzy taste on them. Similar results were obtained by Redondo et al [20], who pointed out that carbonated carrot juice maintained a better taste by the impartation of a 'fizzy' taste to the juice. Redondo et al [20] also pointed out that one of the sensory attributes of soft drinks is the impartation of a fizzy taste sensation when these beverages are consumed.…”
Section: Sensory Evaluationsupporting
confidence: 88%
“…Similar results were obtained by Redondo et al [20], who pointed out that carbonated carrot juice maintained a better taste by the impartation of a 'fizzy' taste to the juice. Redondo et al [20] also pointed out that one of the sensory attributes of soft drinks is the impartation of a fizzy taste sensation when these beverages are consumed. This special fizzy taste sensation was the main reason for the wide acceptability of carbonated beverages over non-carbonated ones.…”
Section: Sensory Evaluationsupporting
confidence: 88%
“…Among the 14 sensory attributes there are taste and mouthfeel sensations. These two are considered to be the main preference factors when choosing a beverage (Redondo, Gomez‐Martinez, & Marcos, 2014). J.Gasco tonic water is characterized mainly by intensive sour taste and aftertaste, carbonation, and the feeling of bite (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…Healthiness is considered the opposite of tastiness, as consumers are more likely to have negative hedonic responses to drinks labelled “healthy.” Moreover, labelling sports drinks as “low-fat,” “low-sugar,” and “no-artificial-flavours” reduces perceived pleasantness (Redondo et al, 2014; Wardle and Huon, 2000). Prior research indicates that specific associations of colour with taste, influence the consumption of coloured beverages (Genschow et al, 2012).…”
Section: Hypothesis Developmentmentioning
confidence: 99%